Chromatographic separation of galactosylkojic acid - Yamamoto, Shuichi; Nakanishi, Kazuhiro; Hassan, Mohd Ali (Elsevier Sci B.V.Amsterdam, 1997)
The mechanism of the separation of galactosylkojic acid (GKA) produced by the reaction of immobilized β-galactosidase with kojic acid (KA) and lactose as substrates using Toyopearl HW40 size exclusion chromatography was investigated. The effects of the mobile phase conditions (salt concentration and pH) on the distribution coefficient K for GKA and KA determined from the peak retention volume were investigated. The K values for GKA and KA decreased slightly when the pH in the mobile phase was increased from 6 to 7, while a further increase in the pH from 7 to 8 caused a considerable decrease in the K values. The K values increased with increasing NaCl concentration (0 to 0.5 M), especially at pH 8. The K value for GKA at pH 8 was almost the same as that for neutral sugar having the same molecular weight. As the gels have negative charges at pH 6-8 and the dissociation constant of KA is ca. 10-8, these results indicate that the distribution of GKA and KA is governed by hydrophobic interaction adsorption and electrostatic repulsion. Although complete baseline separation of GKA was achieved under any of the conditions examined, on the basis of the plate height and K value data the optimum mobile phase conditions were determined to be pH 7 and 50 mM NaCl.; The mechanism of the separation of galactosylkojic acid (GKA) produced by the reaction of immobilized β-galactosidase with kojic acid (KA) and lactose as substrates using Toyopearl HW40 size exclusion chromatography was investigated. The effects of the mobile phase conditions (salt concentration and pH) on the distribution coefficient K for GKA and KA determined from the peak retention volume were investigated. The K values for GKA and KA decreased slightly when the pH in the mobile phase was increased from 6 to 7, while a further increase in the pH from 7 to 8 caused a considerable decrease in the K values. The K values increased with increasing NaCl concentration (0 to 0.5 M), especially at pH 8. The K value for GKA at pH 8 was almost the same as that for neutral sugar having the same molecular weight. As the gels have negative charges at pH 6-8 and the dissociation constant of KA is ca. 10-8, these results indicate that the distribution of GKA and KA is governed by hydrophobic interaction adsorption and electrostatic repulsion. Although complete baseline separation of GKA was achieved under any of the conditions examined, on the basis of the plate height and K value data the optimum mobile phase conditions were determined to be pH 7 and 50 mM NaCl.